Flowering phenology and the interrelations between phenological stages in apple trees (Malus domestica Borkh.) as influenced by the Nordic climate. (19th May 2017) - Rivero, R.; Sønsteby, A.; Heide, O. M.; Måge, F.; Remberg, S. F.
ABSTRACT: In order to assess to what degree the ongoing global warming has affected flowering time of apple trees in the Nordic climate, we studied flowering phenology of trees in an orchard in Southern Norway. Correlation analysis of a 70-year (1946–2016) data series for flowering time of the cultivar 'Gravenstein' revealed a close relationship of the flowering phenophase with April–May heat accumulation ( r = −0.98). Over the last 50-year period, flowering was advanced by 16 days in response to the temperature rises. Similarly, on average for 12 cultivars of varying earliness, flowering was advanced by 9 days over the latest 30-year period (1986–2016). Furthermore, the interrelationship between various phenological stages and floral morphogenesis of the same cultivars in the years 2013 and 2014 was studied, and related to flower-bud formation. The different stages of floral morphogenesis were identified, presented and used as a basis for assessment of flower-bud development in serial dissections. Floral initiation in spurs of actively growing trees took place in late July, approx. 8 weeks after full bloom, whereas in extension shoots, initiation took place after growth cessation in August, approximately 2 weeks later. Decreasing temperatures in mid-August coincided with the cessation of growth and floral initiation in extension shoots, suggesting that the processes may be causally related. The results show that, in the Nordic climate, the period between blooming and initiation of new floral primordia is considerably shorter than in warmer climates, suggesting that the period is only marginally long for completion of shoot growth, and hence, timely floral initiation. This may be an important reason for the irregular flowering and frequent incidences of alternate bearing in apple trees in the cool Nordic climate. The presented information can be useful for determination of the correct timing of flower and fruit thinning to counterbalance biennial bearing.